Boda Bodas and Road Traffic Injuries in Uganda: An Overview of Traffic Safety Trends from 2009 to 2017. (16th November 2020) - Feng, Austin Y; Vaca, Silvia D; Ku, Seul; Jin, Michael C; Kakusa, Bina; Ho, Allen L; Zhang, Michael; Fuller, Anthony; Haglund, Michael M; Grant, Gerald A
Abstract: INTRODUCTION: Road traffic injuries (RTIs) are an important contributor to the morbidity and mortality of developing countries. In Uganda, motorcycle taxis, known as boda bodas, are an increasingly popular source of transportation that is responsible for a growing proportion of RTIs. This study seeks to evaluate traffic safety trends from the past decade and provide recommendations for reducing RTIs. METHODS: Traffic reports from the Ugandan police force (2009 to 2017) were analyzed for RTI characteristics, including severity, driver demographics, and regional distribution. Furthermore, one month of casualty ward data in 2015 and 2018 were collected from the Mulago National Referral Hospital and reviewed for casualty demographics, admission reason, trauma type, etc. RESULTS: Young males were the most common group involved in RTIs (73.95% males; 25–34 years). RTI motorcycle contribution rose steadily from 2009 to 2017 (24.5% to 33.9%) with a greater proportion of motorcyclists involved in fatal accidents. While the total number of crashes dropped from 22, 461 to 13, 244 between 2010 and 2017, the proportion of fatal RTIs increased from 14.7% to 22.2%. In the casualty ward, RTIs accounted for a greater proportion of patients and traumas in 2018 compared to 2015 (10%/41% and 36%/64%, respectively). CONCLUSION: Although RTIs have seen a gross reduction in Uganda, they have become more deadly, with greater motorcycle involvement. Hospital data demonstrate a rising need for trauma and neurosurgical care to manage greater RTI patient burden. Combining RTI prevention, severity reduction, and improvements in the care pathway for these patients may mitigate current RTI trends.